Anti-MRSA activity of curcumin in planktonic cells and biofilms and determination of possible action mechanisms. (June 2021) - Batista de Andrade Neto, João; Pessoa de Farias Cabral, Vitória; Brito Nogueira, Lavouisier Frankilin; Rocha da Silva, Cecília; Gurgel do Amaral Valente Sá, Lívia; Ramos da Silva, Anderson; Barbosa da Silva, Wildson Max; Silva, Jacilene; Marinho, Emmanuel Silva; Cavalcanti, Bruno Coelho; Odorico de Moraes, Manoel; Nobre Júnior, Hélio Vitoriano
Abstract: Staphylococcus aureus is a commensal bacterium and opportunistic human pathogen that can cause a wide variety of clinical infections. It is recognized for its ability to acquire antimicrobial resistance, so methicillin-resistant Staphylococcus aureus (MRSA) infections are a global healthcare challenge. Therefore, the development of new therapeutic options and alternative therapies for treatment is necessary. Curcumin, a polyphenolic substance found in the rhizome of turmeric longa L, has been shown to have several therapeutic properties, including antimicrobial activity. The objective of the study was to evaluate the in vitro antibacterial activity of curcumin alone and associated with oxacillin against MRSA strains, to analyze the mechanism of cell death involved in the isolated action of curcumin by means of flow cytometry and molecular docking, and to verify its superbiofilm action. Curcumin showed antibacterial activity in the range of 125–500 μg/mL against the tested strains, since it caused an increase in membrane permeability and DNA fragmentation, as revealed by flow cytometry analysis. Moreover, it was possible to observe interactions of curcumin with wild-type S. aureus DHFR, S. aureus gyrase and S. aureus gyrase complex with DNA, DNA (5′-D(*CP*GP*AP*TP*GP*CP*G)-3′) and Acyl-PBP2a from MRSA by molecular docking. Curcumin also had a synergistic and additive effect when associated with oxacillin, and significantly reduced the cell viability of the analyzed biofilms. Thus, curcumin is a possible candidate for pharmaceutical formulation development for the treatment of MRSA infections. Highlights: Curcumin showed antimicrobial activity against MRSA. Curcumin showed antimicrobial activity against biofilms of MRSA. Combinations between curcumin and oxacillin showed synergistic and additive interactions against MRSA cells. Curcumin caused changes in membrane integrity and DNA fragmentation.